The Medical Doctor Knowledge, Medical Resume, BPJS Claim Process, and Doctor Compliance Behavior to Filling a Medical Resume At X Hospital Jatinegara - Adisti Indah Lestari; Endang Ruswanti; M. Reza Hilmy (Journal of Multidisciplinary Academic, 2020)
This study aims to determine claim process on Indonesian health insurance (BPJS Kesehatan) related to administration for medical doctors related knowledge, medical resumes, and doctors' compliance in filling out medical resumes. The research approach with a quantitative method using path analysis design. The primary data collection method was obtained through observation with 100 medical record documents, sample counting using the Slovin formula with secondary data by in-depth interviews over five informants, doctor in charge of the patient, medical record officer, BPJS officer and two management people. The results showed knowledge had a significant effect on the compliance behaviour of doctors in filling the Medical Resume, compliance behaviour showed a significant effect on the BPJS claim process, and knowledge showed a significant effect on the BPJS claim process. Thus, the research findings related to the BPJS claim process occurred due to incomplete medical records especially data support, identity data with doctor's diagnosis and incorrect code entry. The implication of the research results for hospital management is necessary to increase the supervision of filling the Medical Resume in collaboration with the medical committee team. Problems found in filling out the Medical Resume are discussed and resolved together by involving all stakeholders.